Clinical characteristics of subjects with a missense mutation in glucokinase. - Page, R; Hattersley, A; Levy, J; Barrow, B; Patel, P; Lo, D; Wainscoat, J; Permutt, M; Bell, G; Turner, R (1995)
The clinical characteristics of subjects with a missense glucokinase mutation, gly299-->arg, were studied in a large pedigree, BX, initially characterized by some members having Maturity Onset Diabetes of the Young (MODY). Glucose tolerance, beta cell function and insulin sensitivity were measured with Homeostasis Model Assessment (HOMA) and with a 'Continuous Infusion of Glucose with Model Assessment' (CIGMA) test. Diabetic complications were clinically assessed. Subjects with glucokinase gly299-->arg were the same age, height, and obesity as the subjects without the mutation. Diabetes was usually asymptomatic at diagnosis and was treated with diet alone in 15 of the 18 subjects. Five of the 11 adult females had been diagnosed when they developed gestational diabetes. The fasting plasma glucose concentrations at the time of study were 4.3-12.6 mmol l-1, with the higher levels being in the more obese (p < 0.05) and in the older subjects (p < 0.05). In subjects with the mutation, beta cell function was impaired, being geometric mean 63% (normal-100%) compared with 126% in the subjects without the mutation (p < 0.001) measured by HOMA and in a subset assessed by CIGMA 59% and 127% (p < 0.01), respectively. There was no difference in fasting insulin concentrations, insulin sensitivity, lipid concentrations or blood pressure between the groups. The haemoglobin A1c was raised (mean 6.5% compared with 5.5% in the subjects without the mutation), but microvascular and macrovascular complications were uncommon. The subjects with the mutation did not have microalbuminuria but had an impaired vibration perception threshold compared with subjects without the mutation.(ABSTRACT TRUNCATED AT 250 WORDS)